Aging Alone in Malaysia: Social Challenges and Legal Protections - Mohd Yusoff, Jal Zabdi; Tahir, Zulazhar; Jamaluddin, Siti Zaharah (Hasanuddin Law Review, 2026)
According to The Japan Times, nearly 28,000 elderly individuals in Japan will die alone in the first half of 2024. This alarming trend is not unique to Japan; many countries, including Malaysia, are facing the challenges of an aging population. As Malaysia approaches becoming an aging nation, issues affecting the elderly, particularly those living alone, demand urgent attention. While not all elderly people face the same circumstances, some enjoy stable finances or live with their family, while others live in isolation due to various factors, such as remaining unmarried, widowhood, or estranged familial ties. Some are simply separated by their distance from their children, who live elsewhere. The growing number of elderly individuals living alone has raised concerns about social neglect and the risk of dying unnoticed. The aim of this article is to examine the issue and challenges faced by the elderly living alone and to assess the legal framework that protect their rights in Malaysia. Using a doctrinal legal research approach, the authors examined the legal frameworks in Malaysia, Singapore and the United Kingdom on the rights and protections of elderly living alone. The findings reveal significant legal gaps in protection and social support available for elderly living alone in Malaysia. This article proposed the need to strengthen the existing legal framework, enhance social supports and foster community initiatives for elderly living alone, ensuring that no one is forgotten.